2018
DOI: 10.1088/1361-665x/aab865
|View full text |Cite
|
Sign up to set email alerts
|

3D interlock design 100% PVDF piezoelectric to improve energy harvesting

Abstract: Piezoelectric textile structures based on 100% poly(vinylidene fluoride) (PVDF) were developed and characterised. Multifilaments of 246 tex were produced by melt spinning. The mechanical stretching during the process provides PVDF fibres with a piezoelectric β-phase of up to 97% has been measured by FTIR experiments. Several studies have been carried out on piezoelectric PVDF-based flexible structures (films or textiles), the aim of the study being the investigation of the differences between 2D and 3D woven f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…3D fabric structures with more piezoelectric components incorporated are desirable for high‐performance fabric‐based PENGs. As displayed in Figure g, a 3D interlock woven fabric‐based PENG was developed based on 100% melt‐spun piezoelectric PVDF fibers . By comparing the electrical outputs of a 2D plain woven PENG, it was found that the energy harvesting ability of the 3D interlock woven structure was greatly improved.…”
Section: Piezoelectric Nanogeneratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D fabric structures with more piezoelectric components incorporated are desirable for high‐performance fabric‐based PENGs. As displayed in Figure g, a 3D interlock woven fabric‐based PENG was developed based on 100% melt‐spun piezoelectric PVDF fibers . By comparing the electrical outputs of a 2D plain woven PENG, it was found that the energy harvesting ability of the 3D interlock woven structure was greatly improved.…”
Section: Piezoelectric Nanogeneratorsmentioning
confidence: 99%
“…g) A 3D diagonal interlock woven structure PENG developed by fabricating PVDF fibers and conductive fibers. Reproduced with permission . Copyright 2018, IOP Publishing.…”
Section: Piezoelectric Nanogeneratorsmentioning
confidence: 99%
“…Contact-mode poling with an electric field and heating is illustrated schematically in Figure S2. The applied external electric field strength required to achieve permanent polarization of PVDF has been reported to be 100 MV/m [144], 300 MV/m [145], 220 MV/m [146], 2.7±0.1 MV·m -1 [35], and 20 V·μm -1 [147]. The poling conditions were as follows: 50 kV cm −1 was applied at 100 °C to PVDF-TrFE containing BTO and rGO [33].…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
“…Both of these effects were conducive to the improvement of the piezoelectric effect and energy harvesting performance in PVDF-based PENG. The mechanical stretching during processing provided PVDF fibres with a piezoelectric β-phase content of up to 97%, as determined using FTIR spectroscopy [35].…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
See 1 more Smart Citation